Pengaruh Pengembangan Karier Terhadap Produktivitas Karyawan Pada PT. Bank Syariah Indonesia Cabang Kenopan - Isra Mira Norizka; Alfi Amalia (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Human resources are the main factor in driving a company. The success and failure of a company in achieving its goals is determined by its human resources. The company's efforts to achieve its goals do not always run smoothly. Companies are required to develop their human resources so that they can compete amidst the changing times today. This study uses a quantitative method, where this study uses a questionnaire as a data collection tool which is distributed directly to employees of PT Bank Syariah Indonesia, and data analysis techniques use SPSS. The variable used in this study is the independent variable (Career Development) while the dependent variable (Employee Productivity). The number of samples in the results of this study shows that career development has an effect on employee productivity. It is shown that there is an influence between the career development variable (X) on employee work productivity (Y) which is indicated by the tcount value which is greater than ttable, namely the tcount value of 6.738 >ttable 2.160 so that it can be concluded that the career development variable (X) has a positive effect on employee work productivity (Y). The results of the independent variable analysis also show that the independent variable on the dependent variable shows an r square value of 0.777. This means that the independent variable, namely career development (X), has a joint contribution of 77.7% to the dependent variable (Y), namely employee productivity.